Transformation of Sound Cipher Complexes in the History of Musical Art and Their Specific Manifestations in the Work of Composers of the 17th - 21st Centuries - Cherniak, Yevheniia; Barantsova, Irina; Biletska, Maryna; Mitlytska, Viktoriia; Pidvarko, Tetyana (Journal of History Culture and Art Research, 2019)
The article discusses the features of sound cipher complexes in the works of famous composers-representatives of different styles and trends. The phenomenon of monograms in the baroque art of J.S. Bach, the semantics of musical anagrams revealed in the works of R. Schumann and the peculiarities of the manifestation of onamophony in postmodernism also considered. The transformation of separate sound cipher complexes in the historical development and the development of musical art is traced. It is emphasized that when studying musical material containing onamophony, the performer traces the patterns of stylistic changes in composer's thinking, analyzes the semantic features of the musical language, and reveals the author's idea in the process of creating the original interpretation of the work.